Atypical manifestations of multiple myeloma: radiological appearance - Heß, Thomas; Egerer, Gerlinde; Kasper, Bernd; Rasul, Kakil Ibrahim; Goldschmidt, Hartmut; Kauffmann, Günter W. (European journal of radiology, 2006)
Diagnostic procedures performed on patients with multiple myeloma typically reveal lytic bone lesions, osteopenia or osteoporosis, bone marrow infiltration by plasma cells as well as overproduction of immunoglobulin or light chains in the serum or urine. Skeletal manifestations are extremely variable and the unusual forms have been described extensively. Extramedullary plasma-cell tumours (plasmocytoma) are found in about 5% of newly diagnosed patients with multiple myelomas. In this paper we present eight patients with atypical forms of multiple myeloma.
Gesehen am 15.02.2022